2015
DOI: 10.1080/14763141.2015.1024716
|View full text |Cite
|
Sign up to set email alerts
|

Quadriceps effort during squat exercise depends on hip extensor muscle strategy

Abstract: Hip extensor strategy, specifically relative contribution of gluteus maximus versus hamstrings, will influence quadriceps effort required during squat exercise, as hamstrings and quadriceps co-contract at the knee. This research examined the effects of hip extensor strategy on quadriceps relative muscular effort (RME) during barbell squat. Inverse dynamics-based torque-driven musculoskeletal models were developed to account for hamstrings co-contraction. Net joint moments were calculated using 3D motion analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 48 publications
0
32
0
Order By: Relevance
“…Alternatively, the hamstrings might not be highly activated because increasing hamstrings reliance necessitates greater knee extensor moments to counter the hamstrings' knee fl xion moment. 61 However, the MVIC position for the vastus lateralis is obtained with both the hip and knee fl xed to 90°. 54 This is the knee angle at which, in the squat, there is a notable amount of net knee extension moment.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, the hamstrings might not be highly activated because increasing hamstrings reliance necessitates greater knee extensor moments to counter the hamstrings' knee fl xion moment. 61 However, the MVIC position for the vastus lateralis is obtained with both the hip and knee fl xed to 90°. 54 This is the knee angle at which, in the squat, there is a notable amount of net knee extension moment.…”
Section: Discussionmentioning
confidence: 99%
“…The 1RM barbell squat test is a measure of maximum muscular strength of the thigh and hip muscles (quadriceps, the gluteus muscles, hamstrings and hip adductors) 17 and the relative 1RM, 1RM value expressed relative to bodyweight (r1RM), was used. The 1RM barbell squat was performed according to Fysprofilen.…”
Section: Outcome Measuresmentioning
confidence: 99%
“…Based on the muscle attachment, GM showed increased leverage to its superior attachment to the dorsal ilium and was involved primarily in hip extension and lateral rotation [28]. A previous study finding suggested that the GM and RF perform a hip extensor muscle strategy synergistically during the ascending phase of standing squat exercise [32].…”
Section: Discussionmentioning
confidence: 98%